FROM THE HISTORY OF SHORCHI FURNITURE FACTORY - Ergasheva Sayyora Abdusoatovna (Journal Park Publishing, 2024)
This article talks about the history of the establishment of the Shorchi furniture factory as a result of the development of carpentry from crafts and its transfer to an industrial base in the Surkhandarya region of the southern regions of Uzbekistan. The activities of this furniture factory, which was originally established as a carpentry workshop, are covered on the basis of periodical press and archival materials.
Keywords: Carpenter, shop, furniture, Shurchi barber shop, bookshelf, tailoring, shoes.